1998
DOI: 10.1111/j.1559-1816.1998.tb01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in the Effectiveness of Sexual Harassment Awareness Training1

Abstract: Little research has investigated the effectiveness of sexual harassment awareness training videos on potential harassers' knowledge, behavior, or attitudes. A laboratory study was conducted that assessed the effects of a sexual harassment awareness training video on several training outcomes: sexual harassment knowledge, touching behavior, and attitudes associated with the likelihood ofharassing others. Participants' propensity to harass was measured prior to their participation in the study. Results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
62
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 31 publications
0
62
0
Order By: Relevance
“…As a result, we know little about the impact of different sexual harassment training methods on various outcomes. A study by Perry et al (1998), however, suggests that sexual harassment training methods may have differential effects across training outcomes. In Perry et al's (1998) research, videos were effective at improving trainee knowledge about sexual harassment and reducing inappropriate behaviors but did not change attitudes related to the propensity to harass others.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…As a result, we know little about the impact of different sexual harassment training methods on various outcomes. A study by Perry et al (1998), however, suggests that sexual harassment training methods may have differential effects across training outcomes. In Perry et al's (1998) research, videos were effective at improving trainee knowledge about sexual harassment and reducing inappropriate behaviors but did not change attitudes related to the propensity to harass others.…”
mentioning
confidence: 87%
“…And, in fact, a number of studies have found that sexual harassment training has a greater positive impact on men than women (Beauvais, 1986;Blakely, Blakely, & Moorman, 1998;Bonate & Jessell, 1996;Moyer & Nath, 1998). Research suggests that within-gender differences also play a role in training effectiveness, however (see, e.g., Kearney, Rochlen, & King, 2004;Perry, Kulik, & Schmidtke, 1998;Robb & Doverspike, 2001). Sexual harassment training has been shown to be less effective in changing attitudes of men who have a higher proclivity to harass (Robb & Doverspike, 2001) or who report more gender role conflict (Kearney et al, 2004).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Studies examining behavioral outcomes related to harassment training are limited. However, a few studies suggest that training may impact propensity to engage in harassment (Moyer & Nath, 1998;Perry, Kulik, & Schmidtke, 1998) and the incidence of harassment (Williams et al, 1999). Finally, studies examining organizational outcomes suggest that training may have a positive impact on participants' perceptions of the organizational climate (Barak, 1994;Thomann et al, 1989) and a limited impact on job and psychological outcomes (Williams et al, 1999).…”
Section: Preventing Harassment In Organizationsmentioning
confidence: 96%